Early Russian Film Prose. Online Research Team Project - Wanner, Clea (Apparatus. Film, Media and Digital Cultures of Central and Eastern Europe, 2019)
Clea Wanner`s review of the online research team project Early Russian Film Prose https://hum.hse.ru/ditl/filmprose/